The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1159/000158805
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Modulation of α-Adrenoceptor and 5HT Receptor Expression in Blood Vessels

Abstract: In vitro experiments on vascular smooth muscle often fail to reveal phenomena clearly demonstrable in vivo. Several recent observations in our laboratory have revealed the facility to uncover responses mediated by receptors whose functional expression had remained hidden with the standard experimental conditions first employed: conversely manipulation of conditions can selectively hide a particular receptor’s response. Examples include the uncovering of responses to: 5HT1 receptors by raised O2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In addition, we have shown that non-selective depolarization by KCl does not evoke any potentiation of endothelin-1-evoked contractions [19]. Receptorreceptor interactions remain a possibility, and such interactions have been postulated between angiotensin II and α-adrenoceptors [21]. This might explain the different interactions of angiotensin II and various spasmogens, as well as the inability of other agonists, such as U46619 [19] or histamine ( J. E. Nally, N. C. Thomson, M. J. O. Wakelam and J. C. McGrath, unpublished work), to mimic angiotensin II.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, we have shown that non-selective depolarization by KCl does not evoke any potentiation of endothelin-1-evoked contractions [19]. Receptorreceptor interactions remain a possibility, and such interactions have been postulated between angiotensin II and α-adrenoceptors [21]. This might explain the different interactions of angiotensin II and various spasmogens, as well as the inability of other agonists, such as U46619 [19] or histamine ( J. E. Nally, N. C. Thomson, M. J. O. Wakelam and J. C. McGrath, unpublished work), to mimic angiotensin II.…”
Section: Discussionmentioning
confidence: 86%
“…Various authors have demonstrated that placental vessels are much less sensitive to 5-HT than umbilical arteries (Panigel 1962;Mak et al 1984;MacLean et al 1992); this implies that the main role for 5-HT lies in the umbilical vessels. Responses to 5-HT in the feto-placental circulation have been demonstrated by several authors (McGrath et al 1990;Breslin 1991). McGrath et al (1988) have reported that there is no significant difference in response to 5-HT between rubbed (in which the endothelium is removed) and unrubbed preparations of the umbilical artery and vein from late pregnancy.…”
Section: Discussionmentioning
confidence: 87%
“…In the tail artery of Fischer 344 rats, the ␣ 2 -AR antagonists idazoxan and rauwolscine shifted the NE concentration-response curves to the right, while the ␣ 2 -AR agonists UK-14304 and BHT-920 shifted the ␣ 1 -AR agonist methoxamine dose-response curves to the left (41). Other studies have suggested that the effects of postjunctional ␣ 2 -AR may be muted and are only observed when another type of agonist is present (18,26).…”
Section: Discussionmentioning
confidence: 93%